AGO2 localizes to cytokinetic protrusions in a p38-dependent manner and is needed for accurate cell division - Vasiliki I. Pantazopoulou (Nature Portfolio, 2021)
Pantazopoulou et al. find that AGO2 resides in open-ended tunneling nanotubes and close-ended cytokinetic bridges. At the latter location, AGO2 colocalizes with cell division components and the authors show that AGO2 depletion impairs cell division fidelity.